THE EXISTENCE OF MEDIA EDUCATION IN IMPROVING THE QUALITY OF HUMAN RESOURCES - Ahdar, Musyarif (IAIN Ambon, 2019)
Abstract: a contemporary phenomenon describes the life competitive competition. In this regard, which can be advanced is are people who have qualified human resources. Demands and urging mankind to be independent and do not depend on institutions that can recruit later after plunging into the world of work. Because given the employment is getting narrower and more and more unemployment. Therefore, in answering this question in the competent institutions must cultivate human resources. In the world of education has several important elements, one of which is the media. Media merupakan alat komunikasi dan informasi yang dapat mengakses ilmu pengetahuan kepada anak didik. Whether a successful learning process in the world of education is strongly influenced by the role of the media.